222 INFARCT-LIKE MYOCARDITIS IN A PATIENT WITH CORONARY ARTERY DISEASE PRESENTING WITH CHEST PAIN: LOOKING BEYOND THE SIMPLEST DIAGNOSIS. (15th December 2022) - Amelotti, Nicola; Brusamolino, Matteo; Mapelli, Massimo; Baggiano, Andrea; Vignati, Carlo; Campodonico, Jeness; Mattavelli, Irene; Salvioni, Elisabetta; De Martini, Stefano; Agostoni, Piergiuseppe
Abstract: Background: A significant proportion of patients with acute myocarditis (AM) presents with chest pain as their first symptom, with ST-segment elevation, regional myocardial dysfunction and cardiac enzyme release ("infarct-like" pattern). Case description: A 68-year-old patient, already known for coronary artery disease (CAD) who underwent a percutaneous coronary intervention (PCI) with drug eluting stent (DES) implantation of distal left anterior descending artery (LAD) six months before, presented with chest pain at rest. An ECG showed ST elevation in the infero-postero-lateral leads with specular ST-depression in aVL; hsTnI was 5900 ng/L (UNL < 51 ng/L). A coronary angiography excluded acute thrombosis, and showed a normal right coronary artery (RCA), significant (70%) stenosis of proximal LAD and left circumflex artery, both treated with PCI + DES. A transthoracic echocardiogram (TTE) showed hypokinesia of the middle portions of the inferior, posterolateral and inferior interventricular septum (SIV) walls. According to a research protocol ongoing in our hospital in post-myocardial infarction patients, a cardiac magnetic resonance (CMR) was performed 48 hours later, showing signs of acute non-ischemic myocardial damage (myocardial edema involving the whole infero-septal wall, late gadolinium enhancement with subepicardial – non-coronary - distribution at apical and antero-apical septum). A final diagnosis of infarct-like AM was established. No complications occurred during the hospital stay and hsTnI progressively decreased (at discharge 37 ng/L). A 6-month follow-up CMR showed normal biventricular function and kinesis, and absence of alterations in tissue characterization sequences. Conclusion: This case highlights how even patients with a known CAD can present with AM mimicking myocardial infarction. Multimodality evaluation, including CMR, can help make the right diagnosis to avoid unnecessary therapies or procedures (i.e. PCI), especially in case of discrepancy between different clinical findings, (i.e. ST-elevation in the inferior leads with a dominant unscathed RCA, non-occlusive stenosis at angiography, echocardiography wall motion abnormalities in RCA territory).